ON ORGANIZATION OF WORKS ON STANDARDIZATION OF AIR TRANSPORT WITH THE ACCOUNT NATIONAL PRIORITIES - G. N. Gipich; S. Y. Skripnichenko; V. S. Shapkin; A. A. Вogoyavlenskiy; A. I. Pleshakov (Научный вестник МГТУ ГА, 2017)
The article analyzes the organization of works on standardization of air transport of the Russian Federation in the framework of the activities of the Technical Committee on standardization "Air transport", according to national priorities.